REVITALISASI IDENTITAS AGAMA LOKAL UGAMO MALIM DALAM KEHIDUPAN MODERNITAS - Wensdy Tindaon (Studia Philosophica et Theologica, 2018)
The tide of the existence identity of local religion in Indonesia is becoming an ongoing reality in Indonesian society. This situation is inseparable from social construction that misunderstand the faith practiced by local religion in Indonesia. In the understanding of Indonesian society, there is still a presumption that local religion are group of animist, primitive, conservative and godless. In this research, local religion give other perspective about local religion in modernity life. Local religion reconstructs their identity through a new identity that is more easily accepted by the state and society. The existence of local religion is also inseparable from a state that is still not able to provide equal are as citizens. This research focuses on identity of Ugamo Malim that have variety of dinamics and limitations such as others local religion in Indonesia. The experience of the loss and difficulty of maintaining a local religious identity in the past has provided awareness of state recognition. The state becomes a place as well as a guarantee for them in maintaining the continuity of their identity. The various negative stigma attached to local religion disappear as we see in the social life and religiousity of Ugamo Malim.Ugamo Malim who reconstructs their identity in modern life so that it has many similarities with the majority religion. The reconstruction of local religious identities is renewed to be relevant to modern life but without reducing the meaning of their identity. Pasang surut eksistensi identitas agama lokal di Indonesia menjadi realitas yang masih berlangsung di masyarakat Indonesia. situasi ini tidak dapat dilepaskan dari konstruksi sosial atas kesalahpahaman tentang praktik kepercayaan dari agama lokal di Indonesia. Dalam pemahaman masyarakat Indonesia masih ada anggapan bahwa agama lokal sebagai kelompok animisme, primitif, konservatif dan tak bertuhan. Dalam penelitian ini, agama lokal memberikan suatu perspektif baru tentang agama lokal di kehidupan moderen. Agama lokal merekonstruksi identitasnya melalui identitas baru yang lebih mudah ditereeima oleh negara dan masyarakat mayoritas. Eksistensi agama lokal juga tidak terlepas dari negara yang masih belum mampu memberikan hak yang sama sebagai warga negara. Penelitian ini fokus pada Ugamo Malim yang memiliki beragam dinamika dan hambatan di masyarakat Indonesia. Pengalaman atas kehilangan identitas dan sulitnya mempertahankan identitas Ugamo Malim menyadarkan mereka untuk mendapatkan pengakuan dari negara. Negara menjadi jaminan bagi mereka untuk dapat mempertahankan identitasnya. Beragam stigma negatif yang melekat pada Ugamo Malim di hilangkan saat melihat keseharian mereka dan praktik religiusnya di masyarakat. Identitas baru yang di bangun Ugamo memiliki persamaan dengan agama mayoritas di Indonesia. Rekonstruksi identitas religius dibarukan dan menjadi relevan dengan kehidupan moderen tanpa mengurangi makna identitasnya.